A representação da tecnologia nos discursos jornalísticos sobre meio ambiente em reportagens das Revistas Época e Scientific American Brasil - Souza, Karoline Sarraf de (2013)
Human interventions in the environment, through technology and industrial development have provoked demonstrations to raise awareness about environmental issues. But even with discussions covering several centuries, many environmental problems that continue to affect the planet. Natural ecosystems and their conditions of water, air, land and biodiversity undergo continuous transformations, many due to human actions. This context, journalism presents itself as an important means of communication to inform citizens about the environmental issue. This study aims to discuss how to formalize certain discursive representations of technology in texts on environment, print journalism of Brazilian Época’s magazine season and North American and German international Scientific American Brasil’s magazine. We selected two reports, each belonging to one of the magazines. The methodology is based mainly on the concepts of the theories of Mikhail Bakhtin / Volochínov and Michel Foucault. It is proposed to verify they are presented innovations and technological solutions in speeches and, according to the proposal the researcher Renato Dagnino, identify perspective on technology that is interpreted, is deterministic, instrumentalist, substantivist or criticism.